Determining relationship marketing instruments - Che Wel, Che Aniza; Bojei, Jamil (IUP Publications, 2009)
The focus of businesses has shifted from acquiring new customers to placing greater emphasis on retaining customers through relationship marketing. However, currently, there is limited knowledge on Relationship Marketing Instruments (RMIs) that are appropriate in managing customer relationships. This paper aims to explore and empirically test the dimensions of RMIs that are appropriate in managing customer relationships. First, it reviews the concept of RMIs and its important dimensions, followed by reports on the construction and validation of the measure of RMIs. The existing literature on this topic have hypothesized five dimensions of RMIs; however, an exploratory factor analysis discovers that RMIs consist of eight dimensions. The final part of the paper discusses the implications of the findings and directions for future research.